(untitled) (Bulletin of the International Association for Paleodontology, 2022)
We documented striking non-lethal anomalies in the dentition of the common pipistrelle (Pipistrellus pipistrellus) during field work in various parts of Germany over the past twenty years. In 2019 we got knowledge of two bat nurslings (P. pipistrellus, P. pygmaeus) from the Rhine-Main area (Hesse, Germany) with ultimately fatal dental anomalies. The aberrations were documented with high-resolution x-ray techniques. We discuss our results in the context of published, but mostly minor and obvious non-lethal teeth anomalies in bats.